PERILAKU EKSPOR DAN PRODUKTIVITAS PADA USAHA MANUFAKTUR MIKRO DAN KECIL DI INDONESIA: PENDEKATAN MODEL LIMITED DEPENDENT - Edi Kiswanto (Universitas Indonesia) (Jurnal Manajemen Industri dan Logistik (JMIL), 2021)
AbstractThis study examines the role of productivity in explaining Indonesian micro and small manufacturing firms’ export behavior based on a firm-level dataset of micro and small manufacturing survey year 2015 (VIMK15) from Statistics Indonesia. By utilizing the Probit and Tobit model, this study analyses the role of the firm’s productivity, which is proxied by labor productivity and output to cost ratio, on determining firms’ export participation and intensity. The other factor related to productivity and firms’ characteristic is also used as control variables. This study found that labor productivity and output to cost ratio positively and significantly determine export participation and intensity even though its marginal effect plays a minor role in the export behavior. Besides, as measured by CEO education and employment training, human capital contributes a major impact on encouraging firms to participate in the export market. Therefore, providing appropriate and reasonable employee training might support Indonesian micro and small manufacturing firms’ development.